YOUTH SPECIALIST: PROBLEMS OF TRAINING AND DEMAND - L. A. GEGEL; E. O. KAZAKOVA (Высшее образование в России)
The sphere of public administration urgently needs highly qualified specialists capable to realize the set strategic tasks of social, economic and innovative development of Russia. The article views the main problems connected with process of training personnel for work with youth as one of the most important sources of personnel potential formation for youth policy implementation. The importance of the theme is connected with the lack of the effective system for personnel training in this branch. During the analysis of personnel structure of the government departments engaged in youth policy implementation it has turned out that employees with non-core education and, consequently, with weak competences demanded in this sphere prevail. According to the requirements imposed on such experts stated in educational and professional standards, the paper proposes the directions of training process optimization, formulates new tasks for youth work organizers. The unified system of training and retraining personnel engaged in state youth work is to solve the designated problems of youth policy staffing and ensure successful implementation of the youth policy in the Russian Federation.